MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
Menu
Praveenk Grade: 9
        
Find ‘x’ which satisfy the equation.
 
log3xlog4x(log5x – 1) = log5x(log4+log3x)
2 years ago

Answers : (1)

noogler
489 Points
										
x=60
 
(logx/log3 )(logx/log4 )(logx/log5-1)=logx/log5(logx/log4+logx/log3)                               here logx means logex
(logx/log3 )(logx/log4 )(logx-log5/log5)=logx/log5(log3logx+log4logx/log3log4)
(logx)2(logx-log5)=logx(log3logx+log4logx)
(logx)2(logx-log5)=(logx)2(log3+log4)
logx-log5=log3+log4
logx=log3+log4+log5
logx=log(3x4x5)                    loga+logb+logc=log(abc)
logx=log60
x=60
2 years ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies
  • Complete JEE Main/Advanced Course and Test Series
  • OFFERED PRICE: Rs. 15,900
  • View Details
  • Complete JEE Main/Advanced Course and Test Series
  • OFFERED PRICE: Rs. 15,900
  • View Details

Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!! Click Here for details